Intranasal BCG vaccination induces systemic and pulmonary mucosal immune responses against tuberculosis in a goat model - Cuenca-Lara, Patricia; Blay-Benach, Miriam; Cervera, Zoraida; Moraleda, Julia; Sevilla, Iker A.; Garrido, Joseba M.; Singh, Mahavir; López-Soria, Sergio; Vidal, Enric; Domingo, Mariano; Pérez de Val, Bernat (Frontiers in Immunology, 2026)
Early immune containment of mycobacteria at the infection site is key to tuberculosis (TB) vaccine development. Intranasal delivery strategies offer a promising alternative to parenteral BCG vaccination, particularly for pulmonary TB, the predominant clinical form in humans and livestock. This study evaluated the immunogenicity of intranasal BCG and heat-inactivated M. bovis (HIMB) with or without adjuvant, as well as prime-boost strategies combining parenteral BCG or HIMB followed by intranasal HIMB in young goats. Intranasal BCG elicited systemic antigen-specific IFNγ production, with enhanced expansion of CD4+IFNγ+ and CD8+IFNγ+ T-cells, comparable to prime-boost regimens. Intranasal BCG and prime-boosted groups also induced higher local proinflammatory responses at the lung mucosa, including proinflammatory cytokine production, expansion of antigen-specific T-cells, and polarization of alveolar macrophages toward activated proinflammatory phenotype. The results underscore the potential of respiratory mucosal BCG delivery to enhance early immune responses against TB infection and support further investigation into its protective efficacy.